Electrospun Membranes Loaded with Melanin Derived from Pecan Nutshell (Carya illinoinensis) Residues for Skin-Care Applications - Michell García-García; Jesús Salvador Jaime-Ferrer; Fernanda Nayeli Medrano-Lango; Elizabeth Quintana-Rodríguez; Tonatiu Campos-García; Erika Rodríguez-Sevilla; Domancar Orona-Tamayo (Membranes)
This study investigates the incorporation of melanin extracted from pecan nutshell residues into a polyacrylonitrile (PAN) matrix during the electrospinning of microfiber membranes. Melanin concentrations of 0.5, 2.0, and 5.0% w/w were incorporated to enhance the physicochemical and biological properties of the fibers. The melanin-loaded PAN fibers exhibited significant antioxidant activity against DPPH and ABTS radicals, with scavenging rates ranging from 46.58% to 62.77% and 41.02% to 82.36%, respectively, while unmodified PAN fibers showed no activity. Furthermore, the melanin-loaded membranes demonstrated antimicrobial effects. The membranes also exhibited an important enzyme inhibition activity against collagenase (37%), hyaluronidase (22%), tyrosinase (36%), and elastase (33%). Molecular docking studies reveal different potential amino acids of the active sites of aging enzymes that interact strongly with melanin pigment, particularly collagenase, followed by hyaluronidase, tyrosinase, and elastase. These results suggest that the novel melanin-loaded PAN membranes possess promising bioactive properties with potential applications in different skin-care applications.